2011
DOI: 10.1017/s095410201100054x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Antarctic Oscillation, the Pacific–South American modes and the El Niño–Southern Oscillation on the Antarctic surface temperature and pressure variations

Abstract: Abstract:In this study, the impacts of the Antarctic Oscillation (AAO), the Pacific-South American teleconnection (PSA) and the El Niño-Southern Oscillation (ENSO) on Antarctic sea level pressure and surface temperature are investigated using surface observational data, European Centre for Medium-Range Weather Forecasts (ECMWF) 40 Year Re-analysis (ERA-40) and the National Centers for Environmental Prediction-National Center for Atmospheric Research (NCEP-NCAR) re-analysis data from 1958-2001. There is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…A estação Casey é significante em nível de 5% (-0,55), as outras estações são significantes a 1% durante o verão, Davis, Mawson e Mirny apresentam as mais altas correlações negativas com a OA, -0,76, -0,80 e -0,69 respectivamente. Yu et al (2011) e Marshall (2007 também encontraram resultados semelhantes com tendência forte de resfriamento para as estações de Mawson, Mirny, Casey e Amundsen Scott.…”
Section: Verãounclassified
See 1 more Smart Citation
“…A estação Casey é significante em nível de 5% (-0,55), as outras estações são significantes a 1% durante o verão, Davis, Mawson e Mirny apresentam as mais altas correlações negativas com a OA, -0,76, -0,80 e -0,69 respectivamente. Yu et al (2011) e Marshall (2007 também encontraram resultados semelhantes com tendência forte de resfriamento para as estações de Mawson, Mirny, Casey e Amundsen Scott.…”
Section: Verãounclassified
“…A região da Antártica é um componente ativo no sistema climático global, que é influenciado pelos modos de variabilidade climáticos globais, regionais e locais (Yuan, 2004;Yu et al, 2011). O sistema climático global é afetado por vários modos internos de variabilidade que são caracterizados pela diferença dos padrões temporais e espaciais.…”
Section: Introductionunclassified
“…In the positive phase of AAO, there is a belt of positive anomalies in the southern The AO and AAO have profound influences on environmental variables in high latitude regions. For example, Yu et al (2012) used both surface observational data and global models to show that among several climate indices including the AAO, the Pacific-South American teleconnection and ENSO, the most important contribution to the trends of Antarctic sea level pressure and surface temperature comes from AAO. Numerous studies showed that AO and AAO also have far-reaching influences beyond polar regions.…”
Section: Correlations With Aa and Aao Indicesmentioning
confidence: 99%
“…In most cases, the products are freely available and have widespread application in many branches of meteorological and climatological research (Bromwich and Fogt, 2004;Bromwich et al, 2007;Jones and Lister, 2007;Yu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%